(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Sugarcane is an important cash-cum-industrial crop of Bangladesh and mainly cultivated in north-western part of the country where different intercropping systems are available. The experiment was carried out at the Bangladesh Sugarcane Research Institute (BSRI) farm, Ishurdi, Pabna, Bangladesh in two successive years viz. 2008–2009 and 2009–2010 to investigate the profitability of sugarcane (cv. Isd 37) with potato (cv. Cardinal) and mungbean (cv. BINA mung5) as successive intercrops. Two factors included in the experiment viz. Factor A: Row to row distance of sugarcane such as 80 cm (S1), 100 cm (S2) and 120 cm (S3) where potato and Mungbean were intercropped. Factor B: Cutting of sugarcane leaf such as cutting of leaves (C1) and No cutting of leaves (C2). The experiment was laid out following randomize complete block design. For sugarcane cultivation BSRI technique and for intercropping the cultivation systems indicated by Bangladesh Agricultural Research Institute were followed. The cane yield and sugar yield were the highest at 100 cm row to row spacing (RRS) of sugarcane (non-leaf cutting = C0) intercropped with 2 rows (2R) of potato followed by 2R of mungbean (S2C0). The lowest yield of sugarcane was found at 80 RRS (C0) with one row (1R) of potato and 1R of mungbean (S1C0). The effect of light interception on growth and yield of first intercrop (potato) was insignificant but significant for second intercrop. The highest yield of potato tuber was 15.28 t ha–1 in S5 (sole potato) followed by 10.85 t ha–1 in S3C1 (sugarcane under leaf cutting at RRS 120 cm with 3R of potato followed by 3R of mungbean). For the yield of mungbean (2nd intercrop), light interception ratio (%) was significantly lowest in (S3C1) where sugarcane RRS was 120 cm with 3R of potato followed by 3R of mungbean under leaf non-cutting (C0) of sugarcane. The highest adjusted cane yield (170.66 t ha–1), benefit cost ratio (3.49) and LER (2.33) were observed in sugarcane at RRS 120 cm with 3R of potato followed by 3R of mungbean (S3C1). Results of both years indicated that intercrops gave higher land equivalent ratio and net return over sole sugarcane planted while sole sugarcane gave maximum benefit cost ratio compared with other intercrops. Finally, on the basis of results it may be concluded that sugarcane transplanted at RRS at 120 cm with 3R potato followed by 3R of mungbean can be grown as intercrops for higher economic return. J. Bangladesh Agril. Univ. 16(3): 429–436, December 2018